Investigating Natural Fiber Reinforced Polymer Composites, Biocomposites, Bionanocomposites Thermo-Mechanical Attributes Emerging Implementations - Ogah, Ogah Anselm; Archibong, Friday Nwankwo; Pauline, Ojukwu Uju; Mbam, Nwabueze Joseph; Yudhanto, Ferriawan (Journal of Fibers and Polymer Composites, 2024)
Natural fibers are progressively employed in manufacturing polymer composite structures beneficial to automotive, construction, and aerospace industries. The upsurge in the utilization of natural fibers in various industries is ascribed to enhanced awareness of the toxicity of man-made fibers. It is imperative to preserve the ecosystem. Thus, legislators and investigators are brainstorming on substituting conventional materials with earth-friendly resources. Natural fibers are green resources with multifarious advantages over synthetic materials, including ease of processing, reduction of CO2 effusions, biodegradable, recyclable, acceptable thermomechanical attributes and improved compatibility with human health. Therefore, natural fibers are widely applied as modifiers for polymers. Recently, natural fibers reinforced polymeric composites, bio-composites and bionanocomposites are the hot potato of researchers ascribed to their attributes such as having low specific gravity, producing good results without costing a lot of money, earth-friendly, and sustainable among others. Jute, kenaf, coir, and hemp natural fibers derived from plants can be exploited to achieve novel lofty execution polymer composite systems. Thermo-mechanical behavior of natural fiber-reinforced composites, bio-composites and bionanocomposites including stress-strain, bending, failure resistance, impact toughness, temperature and deformation fashion them to be more sustainable and engaging than man-made fibers with exceptional biodegradable hallmark. Thermomechanical analysis (TMA) determines variations in specimen dimensions with varying temperature, time or load at ambient conditions. However, TMA of natural fiber-reinforced polymer composites is limited. Therefore, the review highlights on natural fiber-reinforced polymer composites, bio-composites, bionanocomposites, their crucial thermo-mechanical attributes, and emerging implementations.